Case Report: Histological and Histomorphometrical Results of a 3-D Printed Biphasic Calcium Phosphate Ceramic 7 Years After Insertion in a Human Maxillary Alveolar Ridge - Mangano, Carlo; Giuliani, Alessandra; De Tullio, Ilaria; Raspanti, Mario; Piattelli, Adriano; Iezzi, Giovanna (Frontiers in Bioengineering and Biotechnology, 2021)
(1) Introduction: Dental implant placement can be challenging when insufficient bone volume is present and bone augmentation procedures are indicated. The purpose was to assess clinically and histologically a specimen of 30%HA-60%β-TCP BCP 3D-printed scaffold, after 7-years. (2) Case description: the patient underwent bone regeneration of maxillary buccal plate with 3D-printed biphasic-HA block in 2013. After 7-years, a specimen of the regenerated bone was harvested and processed to perform microCT and histomorphometrical analyses. (3) Results: the microarchitecture study performed by microCT in the test-biopsy showed that biomaterial volume decreased more than 23% and that newly-formed bone volume represented more than 57% of the overall mineralized tissue. Comparing with unloaded controls or peri-dental bone, Test-sample appeared much more mineralized and bulky. Histological evaluation showed complete integration of the scaffold and signs of particles degradation. The percentage of bone, biomaterials and soft tissues was respectively 59.2%, 25.6%, 15.2%. Under polarized-light-microscope, the biomaterial was surrounded by lamellar bone. These results indicate that, while unloaded jaws mimicked the typical osteoporotic microarchitecture after 1-year without loading, BCP-sample preserve a correct microarchitecture after 7-years. (4) Conclusions: BCP 3D-printed scaffolds represent a suitable solution for bone regeneration: they can lead to straightforward and less time-consuming surgery, and preserving bone.